471 IMPACT OF COMPLETE REVASCULARIZATION ON DEVELOPMENT OF HEART FAILURE IN PATIENTS WITH ACUTE CORONARY SYNDROME AND MULTIVESSEL DISEASE. (15th December 2022) - Bruno, Francesco; Marengo, Giorgio; Filippo, Ovidio De; Wanha, Wojciech; Leonardi, Sergio; Rubin, Sergio Raposeiras; Fabris, Enrico; Giannino, Giuseppe; Truffa, Alessandra; Gaibazzi, Nicola; Ielasi, Alfonso; Sardella, Gennaro; et al.
Abstract: Background: The impact of complete revascularization (CR) on survival and occurrence of heart failure (HF) after ACS is still unsettled. Goal of this study was to evaluate the impact of CR on HF hospitalization and adverse outcomes in patients with ACS and multivessel coronary artery disease undergoing PCI. Methods: Consecutive ACS patients with multivessel disease from the CORALYS registry were included. First hospitalization for HF or cardiovascular (CV) death was the primary endpoint. Patients were stratified according to CR. Results: Of 14699 patients in the CORALYS registry, 5054 had multivessel disease. 1473 (29.2%) underwent CR, while 3581 (70.8%) did not. Over 5 years follow-up, CR was associated with a reduced incidence of the primary endpoint (adjusted HR 0.66, 95% CI 0.51-0.85), first HF hospitalization (adj HR 0.67, 95% CI 0.49-0.90), CV death (adj HR 0.56, 95% CI 0.38-0.84) and all-cause death (adj HR 0.74, 95% CI 0.56-0.97). The results were consistent in the matched population and in the IPTW analysis. The benefit of CR was consistent across ACS presentations (HR 0.59, 95% CI 0.39-0.89 for STEMI and HR 0.71, 95% CI 0.50-0.99 for NSTE-ACS) and in patients with LVEF>40% (HR 0.52; 95% CI 0.37-0.72), while no significant benefit was observed in patients with LVEF≤40% (HR 0.77; 95% CI 0.37-1.10, p for interaction 0.04). Conclusions: In patients with ACS and multivessel disease, CR reduced the risk of first hospitalization for HF and CV death, as well as first HF hospitalization, CV and overall death. When feasible, CR should be performed in all patients with ACS to reduce the incidence of HF and death. Future studies are needed to assess the evidence of CR in patients with depressed LVEF.